Mengungkap tren teknologi digital dalam pendidikan Islam: tinjauan bibliometrik publikasi ilmiah internasional bereputasi - Mannan, Abd; Tamami, Badrut; Syaifudin, Mokhamad; Niam, Khoirun (LPPM Universitas Ibn Khaldun, Bogor, 2025)
Digital transformation in Islamic education has become a crucial topic since the COVID-19 pandemic, yet systematic analyses remain limited. This study analyzes scholarly publication trends on digital transformation in Islamic education using a bibliometric approach based on 227 publications from the Scopus database (2019–2024), employing VOSviewer to map thematic networks and collaborations. The findings show a significant increase in publications since 2023, with Indonesia and Malaysia as the main contributors. Keywords such as